AUTOLOGOUS OSTEOCHONDRAL GRAFTING FOR OSTEOCHONDRITIS DESSICANS A CASE REPORT - Sanikop, S. T.; Gupta, Srinath M; Chaitanya K., Sri Krishna; Agarwal, Saumya; Chandarana, Vishal S (European Scientific Journal, ESJ, 2015)
Osteochondral defects are common injuries among the young population. Athletes are more prone to these injuries given the amount the stress and strain they put on their lower limbs. The viscoelastic nature of cartilage, which allows load bearing, is disrupted. Early recognition and treatment is needed to prevent Early Osteoarthritis. We are presenting one such case, where a 25 year old male patient with Grade 4 OCD was treated with Autologous osteochondral graft taken from the Non weight bearing part of the femur.